Study of the autonomic function in pregnancy - Araújo, Wagner Santos; Petto, Jefferson; Santos, Alan Carlos Nery dos; Oliveira, Francisco Thiago Oliveira de; Mata, Cauê Santos da; Mantese, João Carlos; Cury, Maria Cristina; Sigulem, Dirce Maria; Gardenghi, Guilliano (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Pregnancy is characterized by physiological changes related to the formation of an ideal environment for the fetus. This period is not unusual occur deviations from normality, as well as imbalance between the various body systems, especially the autonomic nervous system, which can result in pathological conditions. Objective: To evaluate the cardiovascular autonomic function and in accordance with gestational age pregnant women in the 1st, 2nd and 3rd quarter, by studying the Heart Rate Variability (HRV). Method: Were evaluated 20 pregnant women enrolled in a Basic Health Unit. The protocol was divided into two phases with 10 minutes duration in the left lateral decubitus (LLD) and 10 minutes in the sitting position (SEDT). Evaluated: heart rate (HR), Parasympathetic Function (HF) and Function Friendly and influence Parasympathetic (LF), Balance sympathetic / parasympathetic (LF / HF), systolic blood pressure (SBP) and diastolic (DBP) and Respiratory Rate (FR). The DLE phases, SEDT and the transition between them were compared in each trimester. The transitional period and both times were also compared separately according to gestational age. The moments 0min (A), 10min (B) and 20 min (C); were also faced, and finally comparing the quarters 1 (D) 2 (E) and 3 (F). Statistical analysis was applied to Friedman’s analysis of variance. Results: Compared to the steps (0min- x10min- DLE DLE / SEDT x20min- SEDT) in the 1st quarter, there was no significance for HR, SBP, DBP and FR. In the 2nd quarter, when analyzed times (0min- x10min- DLE DLE / SEDT x20min- SEDT) with each other, not reach significance the variables HR, SBP, DBP, RF and LF / HF ratio. By analyzing the times (0min- x10min- DLE DLE / SEDT x20min- SEDT) of the 3rd quarter, it was for HR, SBP, DBP, RF and LF / HF values without significance. Conclusion: This study indicates the existence of significant changes in the autonomic nervous system and cardiorespiratory.